Study to Examine the Extent of Service Fairness On Consumer Behavioral Intention In India With Special Reference To Banking Sector - Singh, Trilok Pratap (International Journal of Psychosocial Rehabilitation, 2020)
The dramatic change in India's economic and industrial dynamics followed the abolition of the very depressed license and the introduction of LPG policy. Since 1991, with modernization and liberalization, market forces have gradually dominated the Indian banking system. The user was the primary beneficiary of the inexorable development and increased competition of broader economies. At the same time, banks find it harder to stop defecting their lucrative clients. This study explores the extent of service fairness for the banking industry in India, particularly in terms of customer behaviour. Findings suggest that customer satisfaction and customer loyalty have a significant impact on service quality, market fairness, and consumer behaviour. This study demonstrates the importance of customer behaviour in Indian bank loyalty.